Remote sounding of the Martian atmosphere in the context of the InterMarsNet mission: General circulation and meteorology - Taylor, F; Calcutt, S; Irwin, P; McCleese, D; Schofield, J; Muhleman, DO; Clancy, RT; Leovy, C (1996)
A concept has been developed for a remote sensing experiment to investigate the physics of the Martian atmosphere from a spin-stabilized orbiter, like that planned for the InterMarsNet mission. Using coincident infrared and microwave channels and limb-to-limb scanning, it can map the planet much more extensively than previously in temperature, atmospheric dust loading, and humidity. When combined with one or more surface stations measuring the same variables, the sounder experiment can contribute to major progress in understanding the general circulation and dust and water cycles of the atmosphere of Mars, and the characterization of medium-scale meteorological systems. Copyright © 1996 Elsevier Science Ltd.